The impact of trauma and how to intervene: a narrative review of psychotraumatology over the past 15 years - Miranda Olff; Irma Hein; Ananda B. Amstadter; Cherie Armour; Marianne Skogbrott Birkeland; Eric Bui; Marylene Cloitre; Anke Ehlers; Julian D. Ford; Talya Greene; Maj Hansen; Nathaniel G. Harnett; et al. (European Journal of Psychotraumatology)
To mark 15 years of the European Journal of Psychotraumatology, editors reviewed the past 15-year years of research on trauma exposure and its consequences, as well as developments in (early) psychological, pharmacological and complementary interventions. In all sections of this paper, we provide perspectives on sex/gender aspects, life course trends, and cross-cultural/global and systemic societal contexts. Globally, the majority of people experience stressful events that may be characterized as traumatic. However, definitions of what is traumatic are not necessarily straightforward or universal. Traumatic events may have a wide range of transdiagnostic mental and physical health consequences, not limited to posttraumatic stress disorder (PTSD). Research on genetic, molecular, and neurobiological influences show promise for further understanding underlying risk and resilience for trauma-related consequences. Symptom presentation, prevalence, and course, in response to traumatic experiences, differ depending on individuals’ age and developmental phase, sex/gender, sociocultural and environmental contexts, and systemic socio-political forces. Early interventions have the potential to prevent acute posttraumatic stress reactions from escalating to a PTSD diagnosis whether delivered in the golden hours or weeks after trauma. However, research on prevention is still scarce compared to treatment research where several evidence-based psychological, pharmacological and complementary/ integrative interventions exist, and novel forms of delivery have become available. Here, we focus on how best to address the range of negative health outcomes following trauma, how to serve individuals across the age spectrum, including the very young and old, and include considerations of sex/gender, ethnicity, and culture in diverse contexts, beyond Western, Educated, Industrialized, Rich, and Democratic (WEIRD) countries. We conclude with providing directions for future research aimed at improving the well-being of all people impacted by trauma around the world. The 15 years EJPT webinar provides a 90-minute summary of this paper and can be downloaded here [http://bit.ly/4jdtx6k].